Scaling the Ivory Tower: Engaging Emergent Identity as Researcher - Harrison, Richard L. (Canadian Journal of Counselling and Psychotherapy, 2008)
This article explores a graduate student’s process of embracing emergent identity as a researcher in the field of counselling, and how this is facilitated through mentoring relationships. I apply concepts from Winnicott’s object relations theory (1958, 1965, 1971) and Lave and Wenger’s (1991) sociocultural model of situated learning to my own experiences of doctoral studies at the University of British Columbia. Through the use of personal narrative informed by these two theoretical perspectives, the article explores and reflects upon how the relationship between research supervisor and graduate student can contribute significantly to the student’s personal and professional development and emerging identity as a researcher and scholar.